Fabrication of polymer coated layered double hydroxide for pharmaceutical applications - Lim, Sei Hien. (2009)
LDHs are promising drug carriers that can accommodate a large pool of anionic drugs into the interlayer for enhancing controlled or site-targeting drug release. However, LDHs cannot be directly injected into human body without any pre-treatment because they will trigger opsonization process and phagocytosis once they enter the human body. In order to prevent the initialization of phagocytosis, the degree of opsonization process has to be minimized. Polyethylene glycol (PEG) can easily achieve this objective but PEG is not readily adsorbed onto LDHs under normal circumstances. Therefore, PEG is first silanized into PEG-OSiCl3 which is reactive enough to be immobilized on the drug-containing LDHs surfaces. The PEG-modified-LDHs are then characterized through FTIR, XRD, XPS, CHN elemental analysis, TGA, zeta potential analysis, FESEM, ICP, UV-Vis spectrometry, BSA protein adsorption and drug release test to study the effect of PEG on LDHs. From the results of FTIR, XRD and XPS, PEG is confirmed to be grafted on drug-containing LDHs. Besides, the composition, surface charges and morphologies of LDHs are determined and they further confirm the grafting of PEG. Moreover, the immobilized PEG successfully reduces the protein adsorption regardless of the varied protein concentration and incubation time. Lastly, PEG is also proven to be effective in enhancing the controlled drug release behavior.